A new species of Hyperlasion Schmitz (Diptera: Sciaridae), causing periodic outbreaks in Japan - Sueyoshi, Masahiro; Nakamura, Shoko; Menzel, Frank (Zootaxa, 2022)
A sciarid species, Hyperlasion breviantenna sp. n., is described from Japan. This is the first record of Hyperlasion Schmitz, 1918, from Asia. We compared the molecular sequence data of the mitochondrial cytochrome c oxidase subunit I (COI) region and external morphological characters among congeners and related genera. Morphological features are described and illustrated, and genetic relatedness to selected species with a one-segmented maxillary palpus is shown as a maximum likelihood tree. The DNA barcoding approach revealed that the genetic sequences of Japanese specimens are identical with those of Australian specimens, which have been assigned to the genus Hyperlasion. The new species occurs in outbreaks during the rainy season, June to July, in Japan and is recognized as a nuisance pest. Newly emerged adults appear in the early morning and enter houses, facilities, and public buildings. The biology of the new species is compared with those of H. wasmanni Schmitz, 1918, and Moehnia erema Pritchard, 1960, which have been recorded as occurring in large aggregations with thousands of individuals abroad, based on published biological notes and reports on these species.